Genome‐wide re‐sequencing of multidrug‐resistant Mycobacterium leprae Airaku‐3. (29th March 2014) - Singh, P.; Benjak, A.; Carat, S.; Kai, M.; Busso, P.; Avanzi, C.; Paniz‐Mondolfi, A.; Peter, C.; Harshman, K.; Rougemont, J.; Matsuoka, M.; Cole, S. T.; et al.
Abstract Genotyping and molecular characterization of drug resistance mechanisms in Mycobacterium leprae enables disease transmission and drug resistance trends to be monitored. In the present study, we performed genome‐wide analysis of Airaku‐3, a multidrug‐resistant strain with an unknown mechanism of resistance to rifampicin. We identified 12 unique non‐synonymous single‐nucleotide polymorphisms (SNPs) including two in the transporter‐encoding ctpC and ctpI genes. In addition, two SNPs were found that improve the resolution of SNP‐based genotyping, particularly for Venezuelan and South East Asian strains of M. leprae.